2018
DOI: 10.1039/c8ra07114d
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced and tunable white light emission from Ag nanoclusters and Eu3+-co-doped CaBAl glasses

Abstract: In this work, Ag:Eu-co-doped calcium boroaluminate glasses were prepared and submitted to further heat treatment to form different Ag species. The optical and luminescence properties were investigated in terms of heat treatment times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…In recent studies, Ag NCs have demonstrated their excellent sensitization ability for RE ions like Eu 3+ , Dy 3+ , Sm 3+ , and Tb 3+ in glasses to acquire enhanced and tunable emission, although the controlling of Ag species cannot be very precise due to the nature of the scaffold structure. , Herein, the energy transfer from Ag NCs to Tb 3+ was realized in FAUY-20Ag y Tb ( y = 2, 5, 10, and 20) zeolites, in which the Ag NCs were well confined inside the cages. Figure a,b shows the corresponding PLE spectra by monitoring Ag NCs emission at 470 nm and Tb 3+ emission at 542 nm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In recent studies, Ag NCs have demonstrated their excellent sensitization ability for RE ions like Eu 3+ , Dy 3+ , Sm 3+ , and Tb 3+ in glasses to acquire enhanced and tunable emission, although the controlling of Ag species cannot be very precise due to the nature of the scaffold structure. , Herein, the energy transfer from Ag NCs to Tb 3+ was realized in FAUY-20Ag y Tb ( y = 2, 5, 10, and 20) zeolites, in which the Ag NCs were well confined inside the cages. Figure a,b shows the corresponding PLE spectra by monitoring Ag NCs emission at 470 nm and Tb 3+ emission at 542 nm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…SMART SYSTEMS: THEORY AND ADVANCES CHAPTER III 61 fluorophosphates Fares, Castro, Orives, Franco, & Nalin, 2017;Fares, et al, 2020;Castro, et al, 2019), zinc borate (Liu, Guo, Ye, Peng, & Zhang, 2015) and CaBAl (Sandrini, et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Eu 3+ doped CABAl glasses (Sandrini, et al, 2018) with Ag nanoclusters showed to be adequate materials for tunable white light emission too. A significant intensity increases in Eu 3+ emission and a lifetime decrease for Ag nanocluster emission were observed under 335 nm excitation, reinforcing the assumption of an energy transfer process.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Ag NCs exhibit brighter emission in Li + partially exchanged LTA zeolites than in the Na + -type counterpart; the emission intensity of Ag NCs can be greatly improved by thermal treatment in FAU zeolites, and the optimized treatment temperature is related to the Ag + loading amount. Ag NCs formatted under a mild thermal activation may not be suitable for lighting applications, as they are not stable enough; however, they can be used for low-content formaldehyde detection . The LTA­(Li)-Ag composite was suggested for humidity sensor application due to its remarkable dynamic change in Ag NCs emission color depending on the hydration level. , Besides, because of their tunable emission in the whole visible range and high quantum yield, Ag NCs have also been employed as sensitizers for f–f transition rare-earth (RE) ions like Eu 3+ , Tb 3+ , and Dy 3+ to improve their excitation efficiency or realize white light and tunable emission. Furthermore, the growth dynamics of Ag NCs and the effect of RE dopants like Tb 3+ on the formation efficiency and chemical state of Ag NCs have been studied using the modified Auger parameter and fluorescence microscopy. , …”
Section: Introductionmentioning
confidence: 99%